2016
DOI: 10.1080/02723638.2016.1191792
|View full text |Cite
|
Sign up to set email alerts
|

From quiet to bold encroachment: contesting dispossession in Accra’s informal sector

Abstract: This article draws on Asef Bayat's theory of "quiet encroachment" to analyse the political agency of street hawkers and squatters in Accra, Ghana. It demonstrates how squatters and street hawkers in Ghana's capital city are engaged in everyday practices of quiet encroachment, whereby they occupy urban space as a means to reproduce themselves. It then explores how encroachers take collective action to defend their access to urban space from stateled dispossession. In a context of competitive partisan politics w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 67 publications
(28 citation statements)
references
References 48 publications
0
27
0
Order By: Relevance
“…The relationship between informality and dispossession is firmly on the intellectual agenda in human geography today (Gillespie, , ; Samson, ). In attempting to theorise and empirically examine this relationship, geographers have engaged with political economy (Glassman, ).…”
Section: Introductionmentioning
confidence: 99%
“…The relationship between informality and dispossession is firmly on the intellectual agenda in human geography today (Gillespie, , ; Samson, ). In attempting to theorise and empirically examine this relationship, geographers have engaged with political economy (Glassman, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, recent studies on resistance have argued that citizens are not just resisters of the poor outcomes of urban governance but activists who, most often, deploy multiple and simultaneous resistance strategies and self-governance practices to cause a change in urban governance (Asante & Helbrecht, 2019a;Lindell, 2008;Lindell et al, 2019;Mitlin, 2018). Recent waves of activism experiment with new kinds of collective action and use a wide spectrum of unconventional forms of contestation (Gillespie, 2017;Mitlin, 2018;Monno, 2016;Obeng-Odoom, 2017;Polanska, 2018). In a 2019 study in Kumasi by Asante and Helbrecht (2019a), they observed that the activism of traders compelled the municipal authority to heed their demands for a written agreement and the right of first refusal during the allocation of trading spaces in the new market.…”
Section: Urban Governance In Ghana and Africamentioning
confidence: 99%
“…Crackdown on Illegal Street traders often results in temporary relief, afterward, the activities continue even on a greater scale [25]. Their activities if left unchecked quietly encroaches on the urban spaces and multiplies to defend their compared territory [26].…”
Section: Assessment Of Street Trading Activities In Public Spaces (Ikmentioning
confidence: 99%